EFEKTIVITAS DAN EFISIENSI PEMAKAIAN DRONE FIXED WING PADA PEMETAAN KEBUN DAN SENSUS POHON KELAPA SAWIT (Elaeis guineensis Jacq) - Megawati Siahaan; Sri Murti Tarigan; Tuty Ningsih; Sandy Simangunsong; Ridho Hikmawan (Institut Teknologi Sawit Indonesia, 2021)
Drone is an unmanned aircraft (Unmanned Aerial Vehicle), which is an electro-mechanical based system that can perform programmed missions, with the following characteristics: (i) unmanned, (ii) operating in fully or partially independent mode, (iii) ) This system is designed to be used repeatedly. The drone is equipped with a high-resolution camera that allows users to monitor a specific location from a height in real time. The use of mapping photos (Mapping Block) using drones is usually used to calculate the principal amount of oil palm trees. This research was using drone fixed wing tipe and was conducted in Tamiang Hulu District, Aceh Tamiang District Nanggroe Aceh Darussalam. This research was conducted from 25-28 August 2020. This study used a descriptive analysis method. The results of this study indicate that the time used to prepare for the use of drones is 30 minutes, for taking aerial photographs and flying time for 25 minutes, combining photos using the Agisoft Photoscane software for 45 minutes, making way points and calculating the number of trees using the Arcgis application for 5 hours, making printout data for 60 minutes, so that the total time for all work is 7 hours 40 minutes for 53.53 hectares, assuming the cost per hectare is Rp.8,583, if with a manual census the time needed is 72 hours, with average costs -average Rp. 56,374, - / ha. Conclution of this research by using drones will be more effective and efficient than manual tree census.